Mechanical measurements of pure and kaolin reinforced hydroxyapatite-derived scaffolds: A comparative study - Obada, D.O.; Dodoo-Arhin, D.; Dauda, E.T.; et al. (Materials Today: Proceedings, 2020)
This study describes the mechanical properties of pure hydroxyapatite (HAp) and kaolin-reinforced hydroxyapatite (K-HAp) is produced from non-separated animal bones using compression pressure under different sintering regimes. The HAp microparticles were synthesized separately using a facile heat treatment method and reinforced with 15 wt% of beneficiated kaolin (HAp/15 wt% BK) using the sol-gel method. The HAp and K-HAp-derived scaffolds were fabricated by cold pressing with a compaction pressure of 500 Pa. Next, the scaffolds were sintered at 900 C, 1000 C, and 1100 C with a 2 h dwell time in the air atmosphere. Subsequently, the mechanical properties of the scaffolds were examined. The effect of sintering temperature and compaction pressure on the hardness and the compressive strength of the pure and reinforced HAp showed that at all points of measurement (with and without compaction pressure), the mechanical properties increased with an increase in sintering temperature, and the most significant mechanical properties were obtained at 1100 C. The values of hardness at the maximum sintering temperature (1100 C) are 0.93 and 1.09 GPa with and without the application of compaction pressure, respectively, for pure HAp-derived scaffolds and 0.74 and 0.78 GPa with and without the application of compaction pressure, for K-HAp-derived scaffolds. The compressive strength for K HAp had the value of 7.84 MPa as compared with 0.69 MPa for the non-reinforced HAp matrix with the application of compaction pressure (500 Pa). The findings show that the mechanical properties of the synthesized kaolin-reinforced HAp about the scaffolds produced with the low compaction pressure of 500 Pa are suitable for human trabecular bone. 2020 The Authors. Published by Elsevier Ltd. This is an open-access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by nc-and/4.0) Selection and Review under the responsibility of the scientific committee of the International. Conference & Exposition on Mechanical, Material, and Manufacturing Technology.
Research Article
Keywords: Hydroxyapatite; Kaolin; Sol-gel; Compaction; Gradient; Mechanical properties